1997
DOI: 10.1021/ja961884i
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Crystal Structure and Electron Density Distribution in the Crystal of Pentaethyl-1,5-dicarba-closo-pentaborane [C2B3(Et)5] at 120 K

Abstract: The molecular and crystal structure and electron density distribution were studied for a single crystal of pentaethyl-1,5-dicarba-closo-pentaborane C 2 B 3 (Et) 5 by the high-resolution X-ray diffraction method at 120 K (5696 observed reflections, R ) 0.056). The single crystal was grown by in situ crystallization with an IR-laser beam producing a molten zone in a Lindeman capillary. In crystal the molecule of the title compound has local C 1 -symmetry with different orientations of the Et-groups with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
5
23
0
1
Order By: Relevance
“…The topology of EDD for nido-5,6-C 2 B 8 H 12 has something in common with that reported for closo-and nido-clusters earlier [8][9][10][11][12][13][14][15][16]. Firstly, the bonding in the cage is realized both via multicenter and two-center bonds of reduced order.…”
Section: Neutral Nido-56-c 2 B 8 H 12supporting
confidence: 77%
See 1 more Smart Citation
“…The topology of EDD for nido-5,6-C 2 B 8 H 12 has something in common with that reported for closo-and nido-clusters earlier [8][9][10][11][12][13][14][15][16]. Firstly, the bonding in the cage is realized both via multicenter and two-center bonds of reduced order.…”
Section: Neutral Nido-56-c 2 B 8 H 12supporting
confidence: 77%
“…The works using AIM were reported only for a limited number of boranes and carboranes and concerned mainly closo species [8][9][10][11][12][13][14][15]. For these types of clusters it was shown that stabilization of electron-deficient systems is achieved both by accumulation of electronic charge along the bond paths and by its delocalization over the polyhedron surface.…”
Section: Introductionmentioning
confidence: 99%
“…For all distances and bonding angles, no significant differences from those in similar compounds [12] are observed. (2) (9) To obtain information on its reactivity, 1a was treated with six equivalents of dimethylamine to form 1c as a colorless, viscous liquid in 88% yield (Scheme 1). Its 11 B NMR spectrum showed a signal at δ ϭ 38.5, confirming that each boryl group had one dimethylamino and one chlorine substituent.…”
Section: 11-tris(dichloroboryl)-33-dimethylbutane (1a)mentioning
confidence: 99%
“…The compositions of the products followed from analytical data and X-ray structure analyses of 1b, 4b, 5b, 6a, and 6f. ( Wiley-VCH Verlag GmbH, 69451 Weinheim, Germany, 2002) pentaborane(5), [6,9] by electron density distribution, [9] and by ab initio computations. [10] We report here on the synthesis and the characterization of 1,1,1-tris(dichloroboryl)-3,3-dimethylbutane and its transformation into 2,3,4-trichloro-1,5-dicarba-closo-pentaborane(5) (6a).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, based on geometric, energetic, and magnetic criteria, the closo-cluster compounds [E 5 H 5 ] 2À (E ¼ B, Al, Ga, In) are nonaromatic, and this offers a possible explanation for why clusters of this type have not yet been synthesized. Currently, only derivatives [12,[59][60][61], such as carbaboranes and a silagallanate [Me 3 SiSi (GaR) 3 GaSiMe 3 ] À (R ¼ Si(SiMe 3 ) 3 ) [62], have been reported.…”
Section: Aromaticity Of [E N H N ] 2à Clustersmentioning
confidence: 99%